COVID-19 and Acute Kidney Injury: A Systematic Review - Sabaghian, Tahereh; Kharazmi, Amir Behnam; Ansari, Ali; Omidi, Fatemeh; Kazemi, Seyyedeh Neda; Hajikhani, Bahareh; Vaziri-Harami, Roya; Tajbakhsh, Ardeshir; Omidi, Sajjad; Haddadi, Sara; Shahidi Bonjar, Amir Hashem; Nasiri, Mohammad Javad; et al. (Frontiers in medicine, 2022)
Acute kidney injury (AKI) has been associated with an increased mortality rate among hospitalized patients with Coronavirus disease 2019 (COVID-19). The current review aimed to evaluate the symptoms, complications, and treatments performed to manage AKI in patients with COVID-19. We searched PubMed/Medline, Web of Science, and Embase for the relevant scientific literature published up to February 1, 2022. The following keywords were used: "COVID-19", "SARS-CoV-2", and "Acute kidney injury". Forty-four studies with a total number of 114 COVID-19 patients with AKI (Mean age: 53.6 years) were included in our systematic review. The most common comorbidities in patients with COVID-19 suffering from AKI were the history of diabetes, hypertension, and hyperlipidemia. Twelve out of the 44 included studies reported a history of chronic kidney disease (CKD) in this group of patients. Focal segmental glomerulosclerosis (FSGS) and acute tubular necrosis (ATN) were the most common pathological evidence. The average length of hospital stay was 19 days, and the average duration of need for mechanical ventilation was 3 days. The current systematic review shows that AKI frequently complicates the course of COVID-19 hospitalizations and is associated with increased severity of illness, prolonged duration of hospitalization, and poor prognosis. Given the extent of the adverse impact of AKI, early detection of comorbidities and renal complications is essential to improve the outcomes of COVID-19 patients.